IMPLEMENT THINK TALK WRITE STRATEGY TO LEVEL IT PROBLEM SOLVING ABILITY MATHEMATICS AND SELF CONFIDENT YUNIOR HIGH SCHOOL STUDENT - Elah Hayati ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This writing is result from research that have go to to to study the leveling of problem solving-ability mathematics and self confident student   mediating school first with strategy think talk write to be compared ordinary studying. This research to design experiment that use it experiment group method and control group pretes-postes. Population in research this is entire student in a Yunior High School in Kabupaten Subang with class student sample VII E and VII F SMP mentioned. the test Type that to be used is the written test in form decomposing. Postes's quantitative data to be based to through test t to normal data and test Mann Whitney to data not normal levely significant     α = 0,05 be obtained that the archievment of problem solving-ability mathematics and self confident student   mediating school first groups experiment better than control group. Gain second groups be analyzed to through test-t to normal data and test Mann Whitney to data not normal be obtained that the leveling of problem solving-ability mathematics and self confident student   mediating school first groups experiment better than control group. To be concluded that studying with strategy think talk write influency better to problem solving ability mathematics and self confident   student VII Yunior High School class than problem solving ability mathematics and self confident   student   who use it ordinary studying .